1981
DOI: 10.1056/nejm198110153051601
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetic Efficacy of High-Dose Metoclopramide: Randomized Trials with Placebo and Prochlorperazine in Patients with Chemotherapy-Induced Nausea and Vomiting

Abstract: In a study of the effectiveness of high intravenous doses of metoclopramide as an antiemetic, 41 patients with advanced cancer who were being treated with cisplatin were entered into two double-blind trials. In the first trial patients were randomly assigned to receive either metoclopramide or placebo, and in the second trial they received either metoclopramide or prochlorperazine. Patients given metoclopramide had significantly fewer episodes of emesis than patients given placebo (medians, 1.0 vs. 10.5; P = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
153
1
4

Year Published

1983
1983
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 676 publications
(160 citation statements)
references
References 13 publications
2
153
1
4
Order By: Relevance
“…In the objective assessment we did not find the measurement of volume of vomitus to be sufficiently reliable to include in the analysis, as others have attempted (Gralla et al, 1981); the volume is also probably of less relevance to the patients than the number of vomiting or retching episodes.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In the objective assessment we did not find the measurement of volume of vomitus to be sufficiently reliable to include in the analysis, as others have attempted (Gralla et al, 1981); the volume is also probably of less relevance to the patients than the number of vomiting or retching episodes.…”
Section: Discussionmentioning
confidence: 75%
“…Newer agents being evaluated are high-dose metoclopramide, dexamethasone and the cannabinoids (Gralla et al, 1981;Trounce, 1982). Most controlled studies of the latter have hitherto been conducted in the United States; those of nabilone have demonstrated useful oral efficacy and superiority over oral prochlorperazine in mixed groups of patients with various malignancies on different chemotherapeutic regimes (Herman et al, 1979;Steele et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Modern medicine is particularly effective at provoking nausea and vomiting, including many drug treatments and post surgery recovery. A significant impetus to develop anti-emetic drugs originated from a desire to inhibit nausea and vomiting produced by some anti-cancer agents with high emetic potential, such as cisplatin (Gralla et al, 1981). An assortment of other drugs also have side effects of nausea and vomiting in prescribed doses, and many drugs will produce these effects at high dosages.…”
Section: Why Are Nausea and Vomiting Important In Today's World?mentioning
confidence: 99%
“…Firstly, it was found that, unlike conventional doses of metoclopramide (Maxolon; Beecham Pharmaceuticals) which antagonise dopamine receptors and stimulate gastric motility, high doses of the drug greatly reduced cis-platin-evoked emesis (Gralla et al, 1981). In contrast, even high doses of the dopamine antagonists, domperidone (Motilium; Janssen Pharmaceuticals) or alizapride, have little or no ability to prevent cis-platininduced emesis (Tonato et al, 1985;Saller & Hellenbrecht, 1985).…”
mentioning
confidence: 99%